ANALISIS KEPATUHAN WAJIB PAJAK TERHADAP PEMBAYARAN PAJAK BUMI DAN BANGUNAN (Studi Kasus Wajib Pajak Desa Paweden, Kecamatan Buaran, Kabupaten Pekalongan) - Mukhamad Fajar Susanto; Imahdah Khoiri Furqon (JEM Jurnal Ekonomi dan Manajemen, 2021)
Land and Building Tax is one of the regional revenues whose potential must be a concern because the object of land and building tax is that some people have it and can increase regional revenues. Some people still think that paying taxes is a burden, so they are reluctant to pay taxes, even though paying taxes is an obligation for taxpayers to be paid. The purpose of this study was to analyze taxpayer compliance in paying land and building taxes. This research is a sampling technique using the cluster sampling method, with as many as 34 taxpayers as respondents. The results of this study conclude that: taxpayer awareness factor has a positive and significant influence on taxpayer compliance in paying Land and Building Tax (PBB). The knowledge factor of taxpayers also has a positive and significant effect on taxpayer compliance in paying Land and Building Tax (PBB).